Micromanufacturing and nanotechnology - Mahalik, N. P. (Nitaigour Premchand) (Springer, 2006)
Micromanufacturing and Nanotechnology is an emerging technological infrastructure and process that involves manufacturing of products and systems at the micro and nano scale levels. Development of micro and nano scale products and systems are underway due to the reason that they are faster, accurate and less expensive. Moreover, the basic functional units of such systems possesses remarkable mechanical, electronic and chemical properties compared to the macro-scale counterparts. Since this infrastructure has already become the prefered choice for the design and development of next generation products and systems it is now necessary to disseminate the conceptual and practical phenomenological know-how in a broader context. This book incorporates a selection of research and development papers. Its scope is the history and background, underlynig design methodology, application domains and recent developments.